Veterinary Allergy Diagnosis: The present and the future with (more) precision. - Martins, Luís (2019)
Veterinary allergy diagnosis needs to follow well-established guidelines under clinical or laboratory approach. Since the 1908s successive proposals have been developed to identify atopic dermatitis in dogs. A first coherent plan has been proposed by Willemse in 1986 undergoing several modifications in 1994. Prélaud and colleagues made important changes to the plan in 1998 and it was further adjusted by Favrot in 2009. It was approved by the International Task Force on Canine Atopic Dermatitis (CAD) in 2010 and subjected to minor updates regarding therapeutics in 2015. For better diagnostic accuracy on sensitization, allergen sources and implicated molecular allergens for animals should be extensively identified. This molecular epidemiology concept is essential for the veterinary allergy diagnosis in the near future as the basis of a component-resolved diagnosis (CRD). It will be highly relevant to increase the efficiency of the avoidance measures and specific immunotherapy. Clinical guidelines lead to at least 80% positive diagnosis of atopy, but newer laboratory methods in veterinary medicine aiming to a more precise diagnosis and a better integration of the clinical/laboratory diagnostic course are needed. Allergoms identification for animals, are a priority in veterinary allergology, aiming the CRD, which is essential to understand possible cross-reactions, allowing a more precise and possibly effective component-resolved immunotherapy (CRIT).